PENGARUH PEMBIAYAAN DEFISIT ANGGARAN TERHADAP INFLASI DAN PERTUMBUHAN EKONOMI: SUATU SIMULASI MODEL EKONOMI MAKRO INDONESIA 1970 – 2003 - Waluyo, Joko (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2006)
The objective of this research is to identify the impact of budget deficit financing oninflation and economic growth. Simulation are conducted using the small open macroeconomics model specified by Waluyo (2005) with 10.000 replication on the stochastic simulation. Using the secondary data of the Indonesian economy from 1970 to 2003, simulation results show that budget deficit financing from foreign debt and monetary policies would increase the economic growth, but inflationary. On the other hand, tax effort policies are considered to be better, since simulation results show that they would improve economic growth without being inflationary.Keywords: budget deficit, macroeconomic model, economic growth, simulation